2018
DOI: 10.1080/10438599.2018.1502394
|View full text |Cite
|
Sign up to set email alerts
|

Does R&D, human capital and FDI matter for TFP in OECD countries?

Abstract: This study investigates the interplay between research & development (R&D), human capital, foreign direct investment (FDI) and total factor productivity (TFP) in OECD.The analysis follows the endogenous growth theory and applies a panel data approach over the period 2000-2015. R&D and human capital have a positive effect on TFP, whilst FDI has a positive and significant effect only in the case of non-European countries. Moreover, the contribution of human capital is higher than that of R&D in European countrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 55 publications
1
14
0
Order By: Relevance
“…Theory suggests that human capital (ibid; Arazmuradov et al 2014;Danska-Borsiak 2018;Akinlo and Adejumo 2016), trade (Bhattacharya et al 2021;Kim 2016), FDI/imports (Bhattacharya et al 2021;Kim 2016;Akinlo and Adejumo 2016;Harris and Moffat 2020), and R&D expenses (Danska-Borsiak 2018;Otsuka 2017;Kim 2016) are the main determinants of TFP growth. However, it is recognized that the latter is the main driver of TFP growth (among others, Saleem et al 2019;Huang et al 2019;Shabbir and Yaqoob 2019;Sharif et al 2021;Pegkas et al 2020;Tsamadias et al 2019;Haider et al 2019;Griliches 1979Griliches , 1994Griffith et al 2004;Edquist and Henrekson 2006;Hall et al 2009;Eberhardt et al 2013;Donghyun et al 2014;Gehringeer et al 2015;Venturini 2015) because it facilitates the adoption and implementation of new technologies exogenously facilitating the domestic production of technological innovations. Productivity gains are linked to R&D diffusion because innovative producers are more receptive to new technologies and thus can maximize gains and reduce costs.…”
Section: The Fie Approach To Measuring Tfp Changementioning
confidence: 99%
See 1 more Smart Citation
“…Theory suggests that human capital (ibid; Arazmuradov et al 2014;Danska-Borsiak 2018;Akinlo and Adejumo 2016), trade (Bhattacharya et al 2021;Kim 2016), FDI/imports (Bhattacharya et al 2021;Kim 2016;Akinlo and Adejumo 2016;Harris and Moffat 2020), and R&D expenses (Danska-Borsiak 2018;Otsuka 2017;Kim 2016) are the main determinants of TFP growth. However, it is recognized that the latter is the main driver of TFP growth (among others, Saleem et al 2019;Huang et al 2019;Shabbir and Yaqoob 2019;Sharif et al 2021;Pegkas et al 2020;Tsamadias et al 2019;Haider et al 2019;Griliches 1979Griliches , 1994Griffith et al 2004;Edquist and Henrekson 2006;Hall et al 2009;Eberhardt et al 2013;Donghyun et al 2014;Gehringeer et al 2015;Venturini 2015) because it facilitates the adoption and implementation of new technologies exogenously facilitating the domestic production of technological innovations. Productivity gains are linked to R&D diffusion because innovative producers are more receptive to new technologies and thus can maximize gains and reduce costs.…”
Section: The Fie Approach To Measuring Tfp Changementioning
confidence: 99%
“…There are thousands of studies on TFP growth in many countries; the following paragraphs review the most recent ones. Tsamadias et al (2019) examined TFP growth among the OEDC countries, dividing the sample countries into two groups, the European Union (EU) members and the non-EU, to account for country heterogeneity for the period 1995-2015. Research and development (R&D) expenditure and human capital (HC) were found to have a positive effect on TFP, while foreign direct investment (FDI) had a positive and significant effect only in the case of non-European countries.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, number of studies identify higher education as determining factor of economic growth, equally in short and long term (Pencavel, 1993;Francis and Iyare, 2006;Permani, 2009;Pegkas and Tsamadias, 2014;Tsamadias, 2019). McMahon (1987) confirms a positive effect of higher education on income growth, but with a time lag of more than seven years.…”
Section: Literature Reviewmentioning
confidence: 99%
“…EF and AC are greater than, equal to, and less than 1, respectively, indicating that the technical performance and technological progress rate remain unchanged or decline, and the technical efficiency is 6 Complexity decomposed into pure technical efficiency index and index scale efficiency. e survey is used to measure the changes in the effectiveness of R&D allocation in 28 provinces and regions in our country from 2014 to 2019 [24]. A general method of estimating capital stock and current capital is the sum of current new capital investment and previous capital minus capital depreciation.…”
Section: Tfpmentioning
confidence: 99%